The economic impact of childhood acute gastroenteritis on Malawian families and the healthcare system. Issue 9 (3rd September 2017) - Hendrix, Nathaniel; Bar-Zeev, Naor; Atherly, Deborah; Chikafa, Jean; Mvula, Hazzie; Wachepa, Richard; Crampin, Amelia C; Mhango, Themba; Mwansambo, Charles; Heyderman, Robert S; French, Neil; Cunliffe, Nigel A; et al.
Abstract : Objectives: This prospective cohort study sought to estimate health system and household costs for episodes of diarrhoeal illness in Malawi. Setting: Data were collected in two Malawian settings: a rural health centre in Chilumba and an urban tertiary care hospital in Blantyre. Participants: Children under 5 years of age presenting with diarrhoeal disease between 1 January 2013 and 21 November 2014 were eligible for inclusion. Illnesses attributed to other underlying causes were excluded, as were illnesses commencing more than 2 weeks prior to presentation. Complete data were collected on 514 cases at both the time of the initial visit to the participating healthcare facility and 6 weeks after discharge. Primary and secondary outcome measures: The primary outcome measure was the total cost of an episode of illness. Costs to the health system were gathered from chart review (drugs and diagnostics) and actual hospital expenditure (staff and facility costs). Household costs, including lost income, were obtained by interview with the parents/guardians of patients. Results: Total costs in 2014 US for rural inpatient, rural outpatient, urban inpatient and urban outpatient were 65.33, 8.89, 60.23 and 14.51, respectively (excluding lost income). Mean household contributions to these costs were 15.8%, 9.8%, 21.3% and 50.6%. Conclusion: This study found significant financial burden from childhood diarrhoeal disease to the healthcare system and to households. The latter face the risk of consequent impoverishment, as the study demonstrates how the costs of seeking treatment bring the income of the majority of families in all income strata below the national poverty line in the month of illness.